A Narrative Review of Recent Advances in Rapid Assessment of Anthocyanins in Agricultural and Food Products - Manzoor, Muhammad Faisal; Hussain, Abid; Naumovski, Nenad; Ranjha, Muhammad Modassar Ali Nawaz; Ahmad, Nazir; Karrar, Emad; Xu, Bin; Ibrahim, Salam A. (Frontiers in Nutrition, 2022)
Anthocyanins (ACN’s) are plant polyphenols that have received increased attention recently mainly due to their potential health benefits and applications as a functional food ingredient. This has also created an interest in the development and validation of several non-destructive techniques of ACN assessments in several food samples. Non-destructive and conventional techniques play an important role in the assessment of ACN's in agricultural and food products. Although conventional methods appear to be more accurate and specific in their analysis, they are also associated with higher costs, the destruction of samples, time-consuming, and require specialized laboratory equipment. In this review article, we present the latest findings relating to the use of several spectroscopic techniques (fluorescence, Raman, Nuclear magnetic resonance spectroscopy, Fourier-transform infrared spectroscopy, and near-infrared spectroscopy), hyperspectral imaging, chemometric based machine learning, and artificial intelligence applications for assessing the ACN content in agricultural and food products. Furthermore, we also propose technical and future advancements of the established techniques with the need for further developments and technique amalgamations.